The relationship between dicsrimination and comorbidity with mental health in the treatment program for TB patients at the Special Pulmonary Hospital in 2025 - Nabilah Rasya Musdah; Zulfendri (Talenta Publisher, 2025)
Tuberculosis (TB) patients often experience discrimination and have comorbidities that have an impact on reducing the quality of life, which ultimately affects mental health in the form of anxiety and depression. This study aims to determine the relationship between discrimination and comorbidities with mental health in the TB patient treatment programme at the Special Pulmonary Hospital. This study used a quantitative approach with a cross sectional design. The population in this study were all TB patients receiving treatment at the Special Pulmonary Hospital whose numbers were unknown, during one month period. The sample in this study was taken using accidental sampling conducted within a period of 1 month with a final number of 73 people. The inclusion criteria were TB patients undergoing treatment who were aged >18 years and consented to participate, while the exclusion criteria included patients with severe clinical conditions or incomplete questionnaire responses. This data was collected by questionnaire and analysed using Spearman's Rank correlation. The results showed that there was a significant relationship between discrimination and mental health of TB patients, namely anxiety (p= 0.0001; r= 0.713) and depression (p=0.0001; r=0.710). In addition, there was a significant relationship between comorbidity and mental health, namely anxiety (p = 0.0001; r = 0.656) and depression (p=0.0001; r=0.642). Comprehensive and systematic integration of mental health services with TB is needed in TB control programmes to accelerate the achievement of the target of complete elimination of TB by 2030.